Antimicrobial and Antibiofilm Activity of Synergistic Combinations of a Commercially Available Small Compound Library With Colistin Against Pseudomonas aeruginosa - Torres, Nelson S.; Montelongo-Jauregui, Daniel; Abercrombie, Johnathan J.; Srinivasan, Anand; Lopez-Ribot, Jose L.; Ramasubramanian, Anand K.; Leung, Kai P. (Frontiers in Microbiology, 2018)
Biofilm-associated Pseudomonas aeruginosa infections remain a significant clinical challenge since the conventional antibiotic treatment or combination therapies are largely ineffective; and new approaches are needed. To circumvent the major challenges associated with discovery of new antimicrobials, we have screened a library of compounds that are commercially available and approved by the FDA (Prestwick Chemical Library) against P. aeruginosa for effective antimicrobial and anti-biofilm activity. A preliminary screen of the Prestwick Chemical Library alone did not yield any repositionable candidates, but in a screen of combinations with a fixed sub-inhibitory concentration of the antibiotic colistin we observed ten drugs whose bacterial inhibiting activity was reproducibly enhanced, seven of which were enhanced by more than 50%. We performed checkerboard assays of these seven drugs in combination with colistin against planktonic cells, and analysis of their interactions over the complete combination matrix using the Zero Interaction Potency model revealed interactions that varied from highly synergistic to completely antagonistic. Of these, five combinations that showed synergism were down-selected and tested against preformed biofilms of P. aeruginosa. Two of the five combinations were active against preformed biofilms of both laboratory and clinical strain of P. aeruginosa, resulting in a 2-log reduction in culturable cells. In summary, we have identified synergistic combinations of five commercially available, FDA-approved drugs and colistin that show antimicrobial activity against planktonic P. aeruginosa (Clomiphene Citrate, Mitoxantrone Dihydrochloride, Methyl Benzethonium Chloride, Benzethonium Chloride, and Auranofin) as well as two combinations (Auranofin and Clomiphene Citrate) with colistin that show antibiofilm activity.